Kepemimpinan Paulus di 1 Korintus 1:10-17: Tinjauan Teologi Pengampunan Miroslav Volf - Jems Mantak; Jessica Elizabeth Abraham; Guntur Hari Mukti (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The fragmentation of the Corinthian congregation recorded in 1 Corinthians 1:10-17 presents a classic leadership challenge that persists in various forms within contemporary churches. While previous studies have examined this text through rhetorical, literary, and biblical-exegetical lenses, the integration of modern theological frameworks remains underexplored. This study aims to integrate a biblical exegesis of 1 Corinthians 1:10-17 with Miroslav Volf‘s theology of forgiveness (Exclusion and Embrace) to reinterpret Paul’s leadership principles. Employing a qualitative library research method, the study proceeds in three stages: syntactical-semantic exegesis of the Greek text, systematic description of Volf‘s concepts of exclusion, embrace, and healing of memory, and an integrative interpretation. The results identify three leadership principles in Paul’s response: christocentricity, relationality, and anti-celebrity cultism. These principles are mapped onto Volf‘s framework, revealing that Paul’s rejection of factionalism functions as an early praxis of “embrace“ that refuses exclusion of the other. The discussion highlights that Volf’s trinitarian model of perichoresis provides a theological grounding for Paul‘s call for unity, while Paul’s concrete leadership strategies offer a biblical foundation for Volf‘s abstract phenomenology. The implications for contemporary church leadership include a three‑dimensional model: theocentric focus, relational‑trinitarian unity, and forgiveness‑based conflict resolution.